HDAC3 functions as a positive regulator in Notch signal transduction. Issue 7 (28th February 2020) - Ferrante, Francesca; Giaimo, Benedetto Daniele; Bartkuhn, Marek; Zimmermann, Tobias; Close, Viola; Mertens, Daniel; Nist, Andrea; Stiewe, Thorsten; Meier-Soelch, Johanna; Kracht, Michael; Just, Steffen; Klöble, Patricia; et al.
Abstract: Aberrant Notch signaling plays a pivotal role in T-cell acute lymphoblastic leukemia (T-ALL) and chronic lymphocytic leukemia (CLL). Amplitude and duration of the Notch response is controlled by ubiquitin-dependent proteasomal degradation of the Notch1 intracellular domain (NICD1), a hallmark of the leukemogenic process. Here, we show that HDAC3 controls NICD1 acetylation levels directly affecting NICD1 protein stability. Either genetic loss-of-function of HDAC3 or nanomolar concentrations of HDAC inhibitor apicidin lead to downregulation of Notch target genes accompanied by a local reduction of histone acetylation. Importantly, an HDAC3-insensitive NICD1 mutant is more stable but biologically less active. Collectively, these data show a new HDAC3- and acetylation-dependent mechanism that may be exploited to treat Notch1-dependent leukemias.